Enzootic bovine leukosis accompanied by splenomegaly in an 8-month-old calf - OKADA, S.; TAGAWA, K.; WADA, R.; YAGUCHI, Y.; KASHIMA, Y.; NISHIMORI, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
In this report, an 8-month-old calf (crossbred, Holstein × Japanese Black) developed fever and accompanied abomasum displacement. Blood chemical test showed remarkably high values of white blood cell count and heteromorphic lymphocytes. In pathological appraisal, enlarged splenomegaly and swelling of the lymph nodes were observed. Histopathological examination revealed invasion of tumor cells derived from B1 cells into systemic lymph nodes, liver and spleen. The provirus loads of bovine leukemia virus (BLV) was 1,439 copies per 10 ng DNA by using real time PCR. In conclusion, this case was diagnosed as bovine leukemia caused by BLV infection with a huge splenomegaly.